TINJAUAN KARAKTERISTIK MARSHALL CAMPURAN ASPHALT CONCTRATE WEARING COURSE (AC-WC) MENGGUNAKAN LIMBAH PLASTIK POLY ETHYLENE THEREPHTHALATE (PET) - Alkam, Moh. Alkam; Desei, Frice L.; Achmad, Fadly (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Negeri Gorontalo, 2023)
Asphalt mixtures have several disadvantages, such as permanent deformation caused by too heavy pressure by truckloads and cracks caused by heat and humidity. In addition, plastic wastes that are increasingly piling up provide opportunities to be used in asphalt mixtures to improve the performance of asphalt mixtures. Concerning this issue, research about the substitution of plastic waste in asphalt mixtures is highly essential to be conducted. Moreover, this research was performed by substituting plastic waste into the asphalt and then mixing it into aggregate. The asphalt weight was taken from optimum asphalt content, while the mixture process was performed at the temperature of + 170°C by employing a high-speed mixing technique to keep the temperature stable during the mixing process. In comparison, the compaction was conducted at the temperature of + 150-160°C. At the same time, the test object was made as many as 25 samples to determine the optimum asphalt content and 25 samples for a mixture of asphalt with plastic waste. The type of plastic used in this research was Polyethylene Terephthalate (PET), with a percentage of plastic waste contents of 0,3%; 0,6%; 0,9%; 1,2%, and 1,5%. The research finding obtained that the highest stability value was 1.176,06 kg at 1,2% plastic content. Specifically, the stability values that met the interim specifications for asphalt plastic mixture were 981,02 kg; 1.152,78 kg; and 1.176,06 kg at plastic contents of 0,6%, 0,9%; and 1,2%, respectively. The highest flow was 3,62 mm at 1,5% plastic content, and the highest MQ was 331,26 kg/mm at 0,9% plastic content. At the same time, the addition of plastic content tended to increase VIM in plastic asphalt mixtures. The VIM values were 3,79%; 4,10%, 4,19%; 4,29%; and 4,33%, respectively. Likewise, the addition of plastic contents could increase VMA values in asphalt mixture where the VIM values were 19,08%; 19,34%, 19,42%; 19,51%; and 19,52%, consecutively. In contrast, adding plastic content to the asphalt mixture could decrease VFA and density values. In detail, the VFA values were 80,15%; 78,81%; 78,41%; 77,99%,, and 77,82% respectively, whilst the consecutive density values were 2,32 gr/cm; 2,32 gr/cm'; 2,31 gr/cm; 2,31 gr/cm'; and 2,31 gr/cm. Based on this analysis result, it could be inferred that 1,2% plastic content was suitable for use in asphalt mixtures with a stability value of 1.176,06 kg. This value increased by 38% from the stability value of conventional asphalt mixtures.